Practice of Self Assessment by Undergraduate Dental Students In Academic Study (Bangladesh Journal of Medical Education, 2012)
This descriptive type of cross sectional study was carried out with the objective of exploring the views of undergraduate dental students about practice of self assessment practice in their academic study at Government & non Government dental colleges in 2009. 1st & 2nd year dental students were the study population here. Sample size was 262.Data was collected by self administered semi structured questionnaire adapting purposive sampling. Study revealed that most of the respondents suggested practice of self assessment is necessary for academic development. The reason behind their practicing of self assessment were stated as because self assessment build self confidence & knowledge, identify gaps & laps of study, improve thyself for better academic performance, helps to build a good professional career & fulfil the aims & goals of life. Regarding the process of self assessment major portion of the respondents followed teachers suggestion & advices of their guardian as their means of self assessment most of the times. Group study, peer feedback, solving previous question, senior students advices & note khatas were used as self assessment tool. In this study it was also found that barriers regarding self assessment were excessive work load in most of the cases 164(70%). On the other hand, self assessment practice was also hampered by lack of facility for group study, non cooperative tendency of the students, lack of feedback from the teachers & frequent examination. Most of the times self assessment practice, factors affecting self assessment & also the barriers regarding self assessment are somehow related to their teachers, guardian & academic examination with the results. So if self assessment practice is being made a provision institutionally it will be beneficial for undergraduate dental students & the institutes. For this it should be ensured that there is proper institutional set up, exact organization, required resources (Faculty, technical support, stuff cooperation) & perfect coordination both intra & inter institutionally all over the country controlled by a central authority. For more information & exact concept as well as proper implementation more & more study can be done regarding self assessment in a wider scale taking all the events of self assessment into consideration. DOI: http://dx.doi.org/10.3329/bjme.v1i1.12853 Bangladesh Journal of Medical Education Vol.1(1) 2010 pp.8-15